Molecular and enological characterization of a natural Saccharomyces uvarum and Saccharomyces cerevisiae hybrid - Pérez-Torrado, Roberto; González, Sara Susana; Combina, Mariana; Barrio, Eladio; Querol, Amparo (2018)
Saccharomyces cerevisiae plays a main role in the winemaking process, although other species, like Saccharomyces uvarum or Saccharomyces paradoxus, have been associated with must fermentations. It has been reported in recent years, that yeast hybrids of different Saccharomyces species might be responsible for wine productions. Although S. cerevisiae × Saccharomyces kudriavzevii hybrids have been well studied, very little attention has been paid to S. cerevisiae × S. uvarum hybrids. In this work we characterized the genomic composition of S6U, a widely used commercial S. cerevisiae × S. uvarum yeast hybrid isolated in wine fermentations containing one copy of the genome of each parental species, which suggests a relatively recent hybridization event. We also studied its performance under diverse enological conditions. The results show enhanced performance under low temperature enological conditions, increased glycerol production, lower acetic acid production and increased production of interesting aroma compounds. We also examined the transcriptomic response of the S6U hybrid strain compared with the reference species under enological conditions. The results show that although the hybrid strain transcriptome is more similar to S. uvarum than to S. cerevisiae, it presents specifically regulated genes involved in stress response, lipids and amino acid metabolism. The enological performance and aroma profile of this S. cerevisiae × S. uvarum hybrid makes it a good candidate for participating in winemaking, especially at low temperatures.